Brain magnetic resonance imaging biomarkers for future frailty; sub‐study of FINGER trial - Pöyhönen, Johanna; Roitto, Hanna‐Maria; Lehtisalo, Jenni; Levälahti, Esko; Strandberg, Timo; Kivipelto, Miia; Antikainen, Riitta; Soininen, Hilkka; Tuomilehto, Jaakko; Laatikainen, Tiina; Solomon, Alina; Stephen, Ruth; et al. (Wiley, 2026)
INTRODUCTION
Brain magnetic resonance imaging (MRI) biomarkers for dementia exist, but little is known about their association with future frailty. We investigated whether baseline brain MRI findings associate with pre-frailty/frailty over 11 years.
METHODS
One hundred twenty participants, aged 60 to 77 years, in the Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) had baseline MRI data. Frailty status (Fried phenotype) was measured at baseline, and at 2, 7, and 11 years. Risk of future pre-frailty/frailty per one standard deviation or one class greater volume/thickness/Fazekas score in baseline MRI was evaluated.
RESULTS
Pre-frailty/frailty was not associated with MRI biomarkers at baseline. Smaller left hippocampal volume was associated with pre-frailty/frailty at 2 (p = 0.042) and 7 years (p = 0.017), and higher load of periventricular white matter hyperintensities (WMHs) at 2 years (p = 0.048), independently of baseline cognition.
DISCUSSION
Smaller left hippocampal volume and higher periventricular WMH score in brain MRI may indicate future frailty risk.